2013
DOI: 10.1271/bbb.130002
|View full text |Cite
|
Sign up to set email alerts
|

Alkaline Pretreatment Improves Saccharification and Ethanol Yield from Waste Money Bills

Abstract: Waste money bills (WMB) is a by-product of the money making process that consists of rich-cellulosic material for many biotechnological applications. This waste money bills is unusable and usually exhausted. Saccharification was improved using various concentrations of sodium hydroxide, NaOH (0.0, 0.5, 1.0, 2.0, 2.5, and 3.0% v/v) and various reaction times (20, 30, and 40 min) during pretreatment at 121 °C. Prior to ethanol fermentation, the highest glucose yield (62.2 mg/mL) was found by pretreatment consist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…According to Ishizawa et al [ 57 ]. and Sheikh et al [ 58 ], the increase in cellulose crystallinity was caused by the lignin removal, which exposed the crystalline cellulose core and increased the glucan content in the solid fraction of pretreated biomass. Other studies have also reported that the crystallinity degree increased slightly when amorphous components (such as lignin and hemicelluloses) were removed [ 12 , 48 , 59 ].…”
Section: Resultsmentioning
confidence: 99%
“…According to Ishizawa et al [ 57 ]. and Sheikh et al [ 58 ], the increase in cellulose crystallinity was caused by the lignin removal, which exposed the crystalline cellulose core and increased the glucan content in the solid fraction of pretreated biomass. Other studies have also reported that the crystallinity degree increased slightly when amorphous components (such as lignin and hemicelluloses) were removed [ 12 , 48 , 59 ].…”
Section: Resultsmentioning
confidence: 99%